PERUBAHAN KANDUNGAN KAROTEN DAN AKTIVITAS ANTIOKSIDAN PADA WORTEL (Daucus carota) SELAMA PROSES PEREBUSAN - Yudiar, Haniel; Lindayani, Linda; Nugrahedi, Probo Y. (VITASPHERE, 2012)
Health is one of the main factors contributing to the quality of life. Good health is resulted from various factors. including the quality and quantity of food intake. Many researches show that nutritional factors contribute in the prevention of degenerative diseases, such as heart disease and cancer. Carrot is one kind of root vegetables that widely consumed, contains health promoting compounds. particularly carotenoids. Boiling is one of ca